From masks to mismanagement: A global assessment of the rise and fall of pandemic-related protests - Sebastian Hellmeier (Research & Politics, 2023)
The Covid-19 pandemic changed contentious politics worldwide. After causing a short-lived decline in global protest activities in early 2020, it has led to the emergence of a variety of pandemic-related protests. While previous work has mostly looked at how event frequencies have changed over time, this paper focuses on changes in protest issues. It applies quantitative text analysis to protest event descriptions and makes the following contributions. First, it traces the rise and fall of pandemic-related protests globally between 2020 and mid-2022, showing that, on average, more than 15% of protest events were pandemic-related. Second, it identifies the most dominant pandemic-related protest issues—masks and vaccination, the economy, business restrictions, health care, education, mismanagement, and crime—and their salience over time. Third, the paper explores potential explanations for differences in the prevalence of pandemic-related protest issues between countries. Multivariate regression analyses suggest a global divide. Protests in developed countries and liberal democracies were more likely about government restrictions. In contrast, citizens in less developed countries took to the streets to demand better healthcare provision.
Additional information: Funding information: "The publication of this article was funded by the WZB Berlin Social Science Center and the Open Access Fund of the Leibniz Association."
Keywords: 300; Protest; pandemic; Covid-19; text-as-data; contentious politics